Predictors of Wound Complications following Radiation and Surgical Resection of Soft Tissue Sarcomas. (15th June 2017) - LeBrun, Drake G.; Guttmann, David M.; Shabason, Jacob E.; Levin, William P.; Kovach, Stephen J.; Weber, Kristy L.
Abstract : Wound complications represent a major source of morbidity in patients undergoing radiation therapy (RT) and surgical resection of soft tissue sarcomas (STS). We investigated whether factors related to RT, surgery, patient comorbidities, and tumor histopathology predict the development of wound complications. An observational study of patients who underwent STS resection and RT was performed. The primary outcome was the occurrence of any wound complication up to four months postoperatively. Significant predictors of wound complications were identified using multivariable logistic regression. Sixty-five patients representing 67 cases of STS were identified. Median age was 59 years (range 22–90) and 34 (52%) patients were female. The rates of major wound complications and any wound complications were 21% and 33%, respectively. After adjusting for radiation timing, diabetes (OR 9.6; 95% CI 1.4–64.8;P = 0.02 ), grade ≥2 radiation dermatitis (OR 4.8; 95% CI 1.2–19.2;P = 0.03 ), and the use of 3D conformal RT (OR 4.6; 95% CI 1.1–20.0;P = 0.04 ) were associated with an increased risk of any wound complication on multivariable analysis. These data suggest that radiation dermatitis and radiation modality are predictors of wound complications in patients with STS.